Integrative model of the leader competences - Figueiredo, p. C. N.; Sousa, M.; Tomé, E. (European Journal of Training and Development, 2022)
Purpose: The aim of the paper is to propose an integrative model of the leader competences through the analysis of the several models of competence found in the literature review. Design/methodology/approach: The methodology used was qualitative, based partially on an integrative literature review (Torraco 2016). This paper aims to review, update and criticize the literature related to the competences approach in the organizational context and, on the other hand, to review, criticize and synthesize the literature, namely, the models and competences. Findings: Difficulties in choosing and implementing a leader competency model led to the integration of competencies in a single model, seeking to simplify the choice and implementation process in organizations. The integrative model of leader competences arises from the literature review, more specifically from the analysis of the different approaches found. This model is grouped into four dimensions – intellectual competences, management competences, social competences and emotional competences. This research is a contribution to reduce the fragmentation of leadership and management theories and facilitates the choice and implementation of a leader competence model suited to the organization’s needs, contributing to the leadership effectiveness. Originality/value: The integrative model of the leader competences allows the choice and implementation of a competence model with a wide range of competences considered as essential in the organizational context by several researchers. This model simplifies the process of identifying the competences that need to be developed, feeding the human resources development process within the organization.